Sentiment analysis of user-generated content in metro service evaluation: a comparative longitudinal study of Sé (São Paulo) and Central do Brasil (Rio de Janeiro) Stations - Souza, Hadassa Abreu Lima; Pinto, Maiara Ferreira; Oliveira, Rodrigo Ribeiro de; Machado, Sivanilza Teixeira; Crespi, Mario Gabriel; Tittonel, Marcelo; Jacintho, Jose Carlos (Brazilian Journal of Production Engineering, 2025)
Metro systems serve as vital organisms for social inclusion and urban mobility in large metropolises. This study analyzes user perceptions of metro services at the busiest stations in São Paulo (Sé) and Rio de Janeiro (Central do Brasil), aiming to identify passenger needs for developing more sustainable mobility infrastructures aligned with UN SDGs 9.1 and 11.2. The research employed longitudinal sentiment analysis of User-Generated Content from Google Maps, covering the period from September 2017 to September 2025 (totaling 3,816 reviews) and processed using DeepSeek-V3.1 Artificial Intelligence. Results reveal predominant criticisms concerning overcrowding, cleanliness, and safety. The Sé station demonstrated higher sensitivity to urban crises (such as "Cracolândia"), while Central do Brasil faced chronic maintenance issues, with Rio's higher fare additionally negatively impacting cost-benefit perceptions. The study concludes that targeted investments in system expansion, safety, and cleanliness are crucial for enhancing passenger experience in both cities' metro systems.
Keywords: Urban Mobility; Metro System; Sentiment Analysis; User-Generated Content; Sustainable Development Goals